Performance Prediction of Spark-Ignition Engine Running on Gasoline-hydrogen and Methane-hydrogen Blends - Mohammed, Kamil; M. M., Rahman (Elsevier, 2015)
Hydrogen is a strong candidate as an alternative fuel and energy carrier which could address problems of environmental pollution, emissions, and geo-political tensions. The aim of this paper is to compare the performance of hydrogen fuel with other fuels and to investigate the power and performance penalty when adding different fractions of hydrogen fuel to the other fuels. A one-dimensional model is developed for an engine with hydrogen and gasoline–hydrogen and methane–hydrogen blends. These models have been calibrated and validated against experimental works and the findings of previous studies. The validation of the pressure trace and the torque showed the predictive capability of the model. Furthermore, the penalty and benefits from hydrogen enrichment were clarified. It was shown that adding small controllable mass factions of hydrogen (<10%) to gasoline enhances the burning velocity and combustion process in the low speed range. However, a small reduction in the output power (<6%) was documented. Adding hydrogen to methane showed greater advantages due to the extremely low burning velocity of methane. The benefits of hydrogen addition are considerably stronger than the limitations. Methane–hydrogen blend seemed more attractive than gasoline–hydrogen blends. It can be seen that the developed simulation codes are powerful tools for the H2ICE community.